Transparansi dan Akuntabilitas dalam Proses Musyawarah Perencanaan Kegiatan Tahunan (MPKT) di Kabupaten Bandung Tahun 2003 - Equitari, Komang Elva; Maryandi, . (Journal of Regional and City Planning, 2004)
Annual activity planning forum, Musyawarah Perencanaan Tahunan (MPKT) of  Kabupaten Bandung 2003, is a new development planning system that is supposed to improve now defunct system called P5D. The principles of good governance, particularly transparency and accountability, are the main guidance in its implementation. However, based on an assessment of transparency and accountability of the process, it is found that the implementation of MPKT in 2003 is still not quite transparent and accountable, particularly in the decision making process